PENGARUH CARA PENGERINGAN TERHADAP MUTU SIMPLISIA SAMBILOTO - Feri Manoi (Pusat Penelitian dan Pengembangan Perkebunan, 2006)
Effect of drying methods to quality of Andrographis paniculata material dryThe study on the effect of drying methods to the quality of sambiloto material dry was con-ducted in the Post Harvest Laboratory, Research Institute for Spice and Medicinal Crops, from April to September 2004. The study aimed to findout the effect of drying methods on quality of sambiloto material dry. The experiment design were used completely randomized design with four treatments and three replications. Treat-ments tested of drying were (1) wind drier, (2) sun, (3) blower, (4) sun and blower combinations. The result showed that the drying methods give a significant effect on quality sambiloto material dry. The treatment of drying sambiloto with was sun and blower combinations to give the best results with lowest water content 8.40%, lowest ash content 7.63%, lowest ash insoluble in Hcl content 0.04%, highest water extractive matter content 26.83%, highest alcohol extractive matter content 14.42 %.